2013
DOI: 10.1038/ncomms3695
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan confinement enhances hydrogen photogeneration from a mimic of the diiron subsite of [FeFe]-hydrogenase

Abstract: Nature has created [FeFe]-hydrogenase enzyme as a hydrogen-forming catalyst with a high turnover rate. However, it does not meet the demands of economically usable catalytic agents because of its limited stability and the cost of its production and purification. Synthetic chemistry has allowed the preparation of remarkably close mimics of [FeFe]-hydrogenase but so far failed to reproduce its catalytic activity. Most models of the active site represent mimics of the inorganic cofactor only, and the enzyme-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(65 citation statements)
references
References 63 publications
0
63
0
Order By: Relevance
“…The use of bio‐inspired [FeFe]‐hydrogenase mimics in HOMPHPs allows reaching very high H 2 production yields; Jian et al (2013) and Wang et al (2013) reported a turnover number (TON) of 52 000 and 27 000 mol H2 / mol cat. , respectively …”
Section: Influence Of System Units On Photocatalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The use of bio‐inspired [FeFe]‐hydrogenase mimics in HOMPHPs allows reaching very high H 2 production yields; Jian et al (2013) and Wang et al (2013) reported a turnover number (TON) of 52 000 and 27 000 mol H2 / mol cat. , respectively …”
Section: Influence Of System Units On Photocatalytic Performancementioning
confidence: 99%
“…The combination of molecular catalysts and quantum dots as photosensitizers, in a system with [FeFe]‐hydrogenase mimics as catalyst, ascorbic acid as electron donor, methanol–H 2 O mixture as solvent and CdTe quantum dots as photosensitizer, has led to TON higher than 50 000 mol H2 /mol cat. Jian et al (2016) compared the performance of CdSe quantum dots and [Ru (bpy) 3 ] 2+ as photosensitizer using [FeFe]‐hydrogenase mimics as catalyst, ascorbic acid as electron donor and H 2 O as solvent. TON of >25 000 mol H2 /mol cat.…”
Section: Influence Of System Units On Photocatalytic Performancementioning
confidence: 99%
“…In related work, Wu and coworkers demonstrated that confinement of the catalyst in a chitosan network, a naturally occurring polysaccharide, results in significant stabilization. They employed a CdTe quantum dot as photosensitizer, and the system is stable for 40 h with a turnover number of up to 52,000, a factor of 4,000 higher than the same components simply free in solution [139]. Unfortunately, the TOF is very low with an initial value of 1 s À1 .…”
Section: Photocatalytic Production Of Hydrogenmentioning
confidence: 99%
“…This short review summarizes recent advances in development of an artificial H 2 ase on the basis of a peptide or protein framework. Hybrid H 2 ases in other combinations, such as dendrimers, sugars and nanomaterials will not be [22][23][24][25][26] discussed.…”
Section: Introductionmentioning
confidence: 97%